Perlindungan Hukum Terhadap Pencipta Lagu Atas Tindakan Remix Lagu Yang Dipublikasi Melalui Tiktok - Sarvina Vanna (INVENTION: Journal of Intellectual Property Law, 2025)
This research aims to find out the legal protection for song creators for the act of remixing songs published through Tiktok.and to find out the legal remedies that can be taken by song creators for the act of remixing songs published through Tiktok. This research uses normative research methods. This research examines the truth based on the suitability between what is studied and the rules set to find a legal rule. The approaches used in this study are the (statue approach), and the (conceptual approach). The result of this study indicate that English translation. The results of this study show that 1) legal protection for song creators for the act of remixing songs through TikTok is a legal protection contained in Law 28 of 2014 article 9 paragraph (3) which states that "Everyone without the permission of the creator or copyright holder is prohibited from reproducing and/or using commercially the work". Then the government provides legal protection with civil remedies in accordance with the application of article 1365 of the Civil Code regarding unlawful acts.